(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The use of historical sources for the reconstruction of climate history is now a method and a study area fully recognized by modern historiography. The vast information in files on catastrophic floods in the Bajio region in addition to provid- ing empirical data on periods of heavy rainfall, yields also information on the use and abuse of certain hydraulic nature farming techniques, particularly flooding irrigation that in the presence of heavy rains caused major floods caused greater steams of water with the consequent material damage and the unfortunate death of people. Rapid population growth in the cities of Celaya, Silao, Irapuato and Leon in the eighteenth century, as a concomitant to mining development, gener- ated a significant demand for agricultural products and manufacturers that re- sulted in the expansion of the productive sector and an increasing intensification of production methods. The multiplication of hydraulic works, both the simple character as complex hydraulic engineering, with its necessary systems of dams, dikes, ditches, streams and puddles deviation of time, eventually had a negative impact on the ecosystems of the region causing repeated flooding that destroyed homes and urban and rural infrastructure, leaving the population unprotected for weeks, months and sometimes years.